Long-term repetitive transcranial magnetic stimulation therapy: new research questions arising from one tinnitus case?. (23rd December 2014) - Labar, Douglas Richard; Cortes, Mar; Edwards, Dylan
Abstract : Tinnitus may become refractory to treatment and disabling. Brain transcranial magnetic stimulation (TMS) has shown promise as a therapy, but has been employed primarily short-term. We treated a patient with 5 weeks of weekly repetitive TMS (rTMS), followed by 6 months of monthly rTMS. He was a 75-year-old dentist with chronic tinnitus from occupational noise exposure. Physical examination and MRIs of the auditory canals and brain had revealed no lesions. The patient showed a general gradual, progressive improvement on per cent of severe tinnitus diary days (from baseline 100% to 33%), tinnitus handicap inventory (from baseline score 70 to 18), and mini-tinnitus questionnaire (from baseline score 17 to 6). No changes occurred in serial audiograms. Transient adverse events were a headache during stimulation, and dizziness 30 min after treatment. Implications and questions for future non-invasive neuromodulation clinical research raised by our case are discussed.